Genomic and phenotypic characterization of multidrug-resistant Salmonella enterica serovar Reading isolates involved in a turkey-associated foodborne outbreak - Sivasankaran, Sathesh K.; Bearson, Bradley L.; Trachsel, Julian M.; Nielsen, Daniel W.; Looft, Torey; Bearson, Shawn M. D. (Frontiers in Microbiology, 2024)
collected after 2017 harbored the uidA and pgdA genes. The truncation event within the cirA gene was also significantly higher in isolates collected after 2017 (74%) compared to before/in 2017 (5%). Phenotypic analysis of the S. Reading isolates for colicin and cefiderocol sensitivities (CirA) and β-methyl-D-glucuronic acid utilization (UidA and accessory proteins) supported the genomic data. Overall, a similar genome reduction pattern was generally observed in both the turkey and human isolates of S. Reading during the outbreak period, and the genetic differences were present in genes that could potentially promote pathogen dissemination due to variation in Salmonella colonization, fitness and/or virulence.